Signal Persistence of Bispectral Index and State Entropy during Surgical Procedure under Sedation - Chanannait Paisansathan; Mukadder D. Ozcan; Qaiser S. Khan; Verna L. Baughman; Mehmet S. Ozcan (The Scientific World Journal)
Introduction. Bispectral index (BIS) and state entropy (SE) are prone to artifacts, especially due to electrocautery (EC). We compared the incidence of artifacts in BIS and SE during surgery under local anesthesia and sedation. Methods. 28 females undergoing breast surgery under local anesthesia and sedation were studied. Simultaneous BIS and SE measurements were recorded every 10 seconds. Artifact was defined as a failure of the device to display a numerical value while the electrodes remained appropriately attached to the patient’s forehead. Ratio of artifact to good signal was compared between BIS and SE in the presence or absence of EC use. Results. 7679 data points were collected from 28 patients. Overall, artifact incidence was similar in BIS and SE (6.2% and 6.3%, resp.). In the presence of EC (1370 data points), BIS had significantly more artifact compared to SE (18.6% versus 6.4%, 𝑃<0.0001). Without EC (6309 data points), BIS had significantly less artifact compared to SE (4.1% versus 7.3%, 𝑃<0.0001). Discussion. BIS and SE were comparable for incidence of artifacts in patients under sedation. Use of EC lead to more artifact in BIS than SE. Conversely, BIS had fewer artifacts than SE when there was no EC use.